National policy and participation in the development of the fishing industry in Malaysia - Mohamed, Mohd. Ibrahim (1989)
The Exclusive Economy Zone (EEZ) concept embodied in UNCLOS III and the importance of fishery to the national economy necessitated the formulation of a comprehensive plan for a rational development and management of the fishing industry in Malaysia. Two national committess on agriculture and exploitation and management of marine living resources were formed in 1978 and 1979 respectively. Subsequently the National Agriculture Policy (NAP) was unveiled in 1984. Based on the NAP a projected expenditure of $M1.44 billion will be invested to develop the fishing industry for the period from 1986-2000. This program which focussed on the national development of the offshore fishing industry and modernization of inshore fisheries is presently implemented. Although there are teetching problems facing the implementation of this program,the performance accomplished thus far seems to meet its objectives. This is supported by a survey conducted on the industry. This paper discusses the status,policy and development plan of the fishing industry in Malaysia.